Developing awareness of confabulation through psychological formulation: A case report and first-person perspective. Issue 2 (17th February 2018) - Fish, Jessica; Forrester, Joseph
ABSTRACT: Confabulation, or the unintentional production of false, distorted or displaced memories, is commonly seen in people who have brain injury. However, it is most common in the acute phase, with persistent confabulation being comparatively rare. In this paper, we describe the case of Joe, a 24-year-old man who showed confabulation in the chronic phase of his rehabilitation, three years after traumatic brain injury. We describe our approach to therapy for this confabulation, and in particular how collaborative formulation enabled Joe to understand his confabulation, and then to manage it effectively, using a diary and "detective" procedure to identify whether or not evidence existed to support potentially confabulated memories. Furthermore, we include Joe's own perspective on what it is like to be confabulating, and on his experience of rehabilitation. This is an example of a successful insight-based therapeutic intervention, which is rare in this domain. To the best of our knowledge, this is also the first example of a first-person perspective on confabulation.